Dimensi Operasional Internal dalam Pendirian Bank Syariah Indonesia (BSI) - Ilmiyah, Izzatul (Journal of Islamic Finance and Syariah Banking, 2023)
Sharia banking is a system created with an alternative mindset, so it is intended to be different from other banks. This system is different not only in terms but also in terms of providing the best service and a sense of security to customers. Then, Bank Syariah Indonesia (BSI) was founded on February 1, 2021. Bank Syariah Indonesia (BSI) can be said to be the largest Sharia bank in Indonesia it was founded as a result of the merger of 3 (three) Sharia banks, namely BNI Syariah, Bank Syariah Mandiri, and BRI Syariah. The merger of these banks is intended to encourage larger Islamic banks to enter the global market. In this research, the researcher uses a library study approach, what is meant by library study itself is a relationship of actions related to procedures for combining library data, understanding and writing, and processing the object of study. The research results show that the internal operational dimension in the establishment of Bank Syariah Indonesia is the BSI organizational structure which consists of a president director, vice president director, wholesale & transactional banking, retail banking, distribution, information technology & operations, risk management & compliance, finance & Treasury, consumer business, operations, special asset management, human capital. BSI's own working mechanism refers to the GMS decision, namely regarding future work plans and accountability reports. BSI directors can carry out further operational steps and bank policies, as well as a fatwa issued by the DPS containing BSI products, the bank's operations and policies have received validity. and within BSI there are 2 (two) types of supervision, including internal supervision carried out by the board of commissioners, DPS, and directors. Furthermore, external supervision is carried out by BI (Bank Indonesia). Lastly, BSI's activities include marketing and operational activities.